Major reduction in asthma morbidity and continued reduction in asthma mortality in New Zealand: what lessons have been learned?. Issue 3 (March 1995) - Garrett, J; Kolbe, J; Richards, G; Whitlock, T; Rea, H
Abstract : Increasing financial barriers to primary health care against a background of social and economic decline are likely to have contributed to asthma morbidity and mortality in New Zealand. Although there would not have been a sufficient increase in asthma prevalence to have accounted for the threefold increase in mortality rates, whether or not there was an increase in asthma severity in the late 1970s remains open to debate. Misuse or poor use of newly available and potent bronchodilator medications by those with the most severe asthma may simply have contributed to further delays in obtaining appropriate care and therefore to an increase in frequency of severe attacks in the community. Despite substantial increases in the use of bronchodilator therapy in New Zealand, there was no immediate improvement in indices of either asthma morbidity or mortality. The initial reduction in mortality rates in the 1980s happened at a time when first admissions for asthma were still increasing and seems to be best explained by an improvement in utilisation of hospital services (which were free until 1992) rather than a reduction in asthma severity. However, the recent reductions in all measures of asthma morbidity and further reduction in asthma mortality since 1989 does now suggest a reduction in asthma severity and would be best explained by the substantial increase in medium and high dose inhaled corticosteroid use, and to the endorsement of the current management strategies for asthma which are being promoted internationally and which were given considerable publicity in New Zealand in 1989 and 1990. Whilst sales of inhaled beta agonists were higher in 1991 than 1989, this may not reflect their pattern of use by individual patients since the need for an increase in inhaled beta agonist treatment has been accepted as indicating a lack of control and the need for either starting or increasing the dose of inhaled steroid treatment.